The Real-time fitness action recognition using LSTM/GRU techniques - Wria Muhamad, Azhee; Ali Mohammed, Aree (The Scientific Journal of Cihan University– Sulaimaniya, 2026)
Human action recognition in fitness refers to the ability of technology to identify and track human movements during the exercise or physical activity. This may include recognizing specific exercises, such as Squats or push-ups, as well as tracking the overall movement patterns and providing feedback on forms and techniques. This technology is often used in fitness apps or wearable devices to help individuals improve their workouts and prevent injury. Using Artificial Intelligence (AI) to recognize human actions in fitness is a great idea. With the help of Artificial Intelligence, fitness enthusiasts can get accurate and real-time feedback on their workout routines, which can help them improve their performance and achieve their fitness goals faster. However, it is important to ensure that the data collected by these devices are secure and not misused in any way. Overall, it is believed that AI has the potential to revolutionize the way we approach fitness and lead to a healthier lifestyle for many people. Recurrent networks consist of distributed parameters that are present in each layer of the network. This study introduces dual models for recognizing many actions, one using LSTM and the other using GRU. An experiment was carried out on the EUCF Sport action dataset to compare the accuracy rates of the two models. The results indicate that both the LSTM and GRU models had significantly better accuracy rates than other state-of-the-art action recognition models, with recorded accuracies of 99.78% and 98.53% respectively on EUCF Sports dataset.